Characterization of Purple Corn Anthocyanin Components and Their Pharmacokinetic Profiles through In Silico Study - Ichda Chayati; Satyo Nuryadi; Hari Purnomo; Isnatin Miladiyah (Integrated Research and Testing Laboratory (LPPT) Universitas Gadjah Mada, 2026)
Purple corn contains high levels of bioactive anthocyanins with potential health-promoting effects. This study aimed to quantitatively characterize the anthocyanin profile of an Indonesian purple corn variety and evaluate the pharmacokinetic properties of its major constituents using in silico modelling. The anthocyanin extract was analyzed by HPLC (high-performance liquid chromatography), and concentrations were determined using authentic standards. The pharmacokinetic parameters, including absorption, distribution, metabolism, excretion, and toxicity (ADMET), were predicted using the pkCSM platform, and drug-likeness properties were evaluated based on Lipinski’s Rule of Five. Cyanidin-3-glucoside (0.82 mg/100 g DW), peonidin-3-glucoside (0.38 mg/100 g DW), and pelargonidin-3-glucoside (0.35 mg/100 g DW) were identified as the predominant anthocyanins. In silico ADMET predictions using pkCSM revealed low intestinal absorption, moderate peripheral tissue distribution, and violations of Lipinski’s Rule of Five, indicating limited suitability as conventional oral pharmaceuticals. Nevertheless, the compounds exhibited low predicted toxicity, minimal CYP450 inhibition, and favorable excretion profiles, supporting potential safe use as nutraceuticals or functional food ingredients. This integrated approach demonstrates that experimental phytochemical profiling combined with computational pharmacokinetic analysis provides valuable insight into the properties of anthocyanins beyond standard bioavailability studies. The findings provide a foundation for future formulation strategies, such as encapsulation or delivery enhancement, to improve bioavailability and functional activity in foods or dietary supplements. Overall, anthocyanins from Indonesian purple corn are promising safe natural bioactives, warranting further experimental and translational research.